2012
DOI: 10.1186/1471-2164-13-420
|View full text |Cite
|
Sign up to set email alerts
|

Genomic arrangement of salinity tolerance QTLs in salmonids: A comparative analysis of Atlantic salmon (Salmo salar) with Arctic charr (Salvelinus alpinus) and rainbow trout (Oncorhynchus mykiss)

Abstract: BackgroundQuantitative trait locus (QTL) studies show that variation in salinity tolerance in Arctic charr and rainbow trout has a genetic basis, even though both these species have low to moderate salinity tolerance capacities. QTL were observed to localize to homologous linkage group segments within putative chromosomal regions possessing multiple candidate genes. We compared salinity tolerance QTL in rainbow trout and Arctic charr to those detected in a higher salinity tolerant species, Atlantic salmon. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 63 publications
6
56
0
1
Order By: Relevance
“…For instance, candidate genes in salmonids show evidence of clustering along linkage groups (Norman et al, 2012) and similar patterns are evident on model teleost chromosomes (e.g. medaka, stickleback, zebrafish) (Norman et al, 2012) and on reconstructed proto-actinopterygian ancestral chromosomes (Kasahara et al, 2007). Current data indicate that interchromosomal rearrangements in the Atlantic salmon genome have produced unique combinations of salinity tolerance candidate genes, which may be related to the high salinity tolerance capacity that is characteristic of this species (Norman et al, 2012).…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…For instance, candidate genes in salmonids show evidence of clustering along linkage groups (Norman et al, 2012) and similar patterns are evident on model teleost chromosomes (e.g. medaka, stickleback, zebrafish) (Norman et al, 2012) and on reconstructed proto-actinopterygian ancestral chromosomes (Kasahara et al, 2007). Current data indicate that interchromosomal rearrangements in the Atlantic salmon genome have produced unique combinations of salinity tolerance candidate genes, which may be related to the high salinity tolerance capacity that is characteristic of this species (Norman et al, 2012).…”
mentioning
confidence: 74%
“…Clustered genes in vertebrates are more likely to be co-expressed (Hurst et al, 2004;Ng et al, 2009;Woo et al, 2010) and co-methylated (McGowan et al, 2011) and thus are more likely to be involved in the same or closely related biological pathways. For instance, candidate genes in salmonids show evidence of clustering along linkage groups (Norman et al, 2012) and similar patterns are evident on model teleost chromosomes (e.g. medaka, stickleback, zebrafish) (Norman et al, 2012) and on reconstructed proto-actinopterygian ancestral chromosomes (Kasahara et al, 2007).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Sun et al [76] located a cold resistance locus on common carp LG5. Rengmark et al [77] reported a high salinity-tolerance gene, while Norman et al [78] compared QTLs for salinity tolerance among the salmonid genomes and found that the QTLs were distributed on nine different LGs.…”
Section: Qtl Analysis For Anti-stress Traitsmentioning
confidence: 99%